Juvenile coat colours in mini-pigs at ICG - S. V. Nikitin; S. P. Knyazev; K. S. Shatokhin; G. M. Goncharenko; V. I. Zaporozhets; V. I. Ermolayev (Вавиловский журнал генетики и селекции, 2017)
This article continues a previous study colors in minipigs at ICG. It also has a phenomenological character, but it consideres juvenile colour, which is an integral element of the ontogenetic formation of the suit, wild type agouti pigs of the species Sus scrofa L. However, in ICG mini pigs, in addition to individuals with the suit of the wild type, juvenile colour is a feature of pigs with the black spotted suit. It should be noted that data about a similar phenomenon in pigs with black spotted colour were not found in the literature. We proposed that a unique juvenile colour of black spotted mini-pigs ICG is a consequence of increased synthesis of pigments of hair, the intensity of which obviously exceeds the performance by the wild boar and domestic pigs. Newborn piglets of mini pigs ICG of the colour of the wild type typically have too little or too much yellow (orange, brown) pigment, which makes the figure of juvenile livery blurry – low contrast, or the lack of it, with the result that they are gray or gray-blue color with dark gray longitudinal stripes. The pattern of juvenile livery piglets of mini pigs ICG is disrupted. As a rule, instead of a longitudinal stripe, a mesh pattern livery is observed. Therefore, the agouti like colour observed in mini-pigs ICG should rather be called more properly pseudowild type. It was suggested that the specially planned crosses were able to “reveal” the genetic load of mutations in the complex of alleles involved in the formation of the suit of the wild type and accumulated in the population, not exposed to stabilizing selection on this archaic for domestic pigs’ colour. The accumulation of this genetic cargo at the mini-pigs was made possible by gipostatic suit wild type relative to epistatic colour standard for modern commercial plant breeds.